Preparation method of pyridine-rich nitrogen type copper monatomic catalyst
By introducing pyridine-rich nitrogen-type copper single-atom catalysts into the electrocatalyst, the problems of low catalytic efficiency and poor selectivity in the prior art are solved, and efficient nitrate reduction of ammonia is achieved, which significantly improves the Faraday efficiency of ammonia production. and yield.
Patent Information
- Application Number
- CN202311028961.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-16
AI Technical Summary
The existing electrocatalysts have low catalytic efficiency and poor selectivity during the process of nitrate reduction in ammonia production, and the metal load of copper single-atom catalysts is low, which affects the selectivity and yield of ammonia production.
By mixing pyrrole monomer, polyethyleneimine and sodium dodecylbenzenesulfonate in HCl solution, a hydrogel was formed, and then copper atoms were adsorbed in CuCl2 solution, and after freeze-drying, carbonization and washing, A pyridine-rich copper single-atom catalyst was prepared.
The catalyst significantly improves the activity of nitrate reduction in an alkaline environment, with a maximum Faraday efficiency of 94.61%, and a yield of 130.71 mgNH3 mgCu-1h-1, which significantly improves the selectivity and yield of ammonia production.
Smart Images

Figure CN119491253A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic material preparation, and in particular to a method for preparing a pyridine nitrogen-rich copper single-atom catalyst and application of the catalyst in nitrate reduction to produce ammonia. Background Art
[0002] The Outline of the 14th Five-Year Plan and the Long-Term Goals for 2035 proposes to promote green development, develop a circular economy, promote the green transformation of my country's development mode, achieve efficient and circular utilization of resources, and promote the realization of dual carbon goals. In March 2022, the "14th Five-Year Plan for New Energy Storage Development Implementation Plan" jointly issued by the National Development and Reform Commission and the National Energy Administration emphasized the expansion of hydrogen and ammonia energy storage application areas, focusing on pilot demonstrations of long-cycle energy storage technologies such as renewable energy ammonia production. Ammonia (NH3) is an important chemical raw material and is also considered a carrier of renewable energy. Its main advantages include high energy density (22.5MJ / kg), green and carbon-free, and high transportation efficiency. At present, the main method for industrial ammonia synthesis is the Haber-Bosch process. However, the Haber-Bosch process requires the combustion of a large amount of fossil fuels to achieve the required high temperature and high pressure, and the early hydrogen production process through methane reforming will also release a large amount of greenhouse gases, causing serious pollution to the environment. Therefore, it is urgent to explore a green and sustainable method for synthesizing ammonia technology to decentralize the traditional synthetic ammonia industry that is energy-intensive and environmentally polluting.
[0003] In recent years, nitrate pollution has become a serious global environmental problem. Its sources are mainly divided into food production industries such as agriculture, animal husbandry, and forestry, and fuel and wastewater emissions from industrial industries. Therefore, converting harmful nitrates into more valuable ammonia can not only solve the environmental problems caused by nitrate pollution, but also is expected to replace the traditional ammonia synthesis process and realize the recycling of resources. However, the electrochemical nitric acid reduction reaction (NO3RR) involves the transfer of 8 electrons and the coupling of 9 protons. The complex electron / proton transfer is bound to reduce the kinetic rate of the reaction and will be accompanied by many intermediates and by-products (such as nitrite, hydrogen, etc.), thereby affecting the Faradaic efficiency (FE) and yield (YR) of NH3. Therefore, designing electrocatalysts with the purpose of solving the above challenges of NO3RR is the best way to achieve efficient ammonia production.
[0004] Carbon materials have the advantages of good conductivity, large specific surface area, high crustal abundance, stable and adjustable structure, etc., and have become one of the most important catalysts or catalyst carriers. In carbon-based metal catalysts obtained by introducing metals into carbon materials, there is usually a strong interaction between the metal and the carbon carrier, which can be used to adjust the electronic structure of the active metal center to achieve efficient catalysis. A large number of carbon-based metal catalysts have been reported in previous literature. The size range of these carbon-based non-metal catalysts includes nanometers, clusters and atoms. Compared with nanocatalysts, single atom catalysts (SACs) have atomically distributed active centers, maximum atomic utilization efficiency, unsaturated coordination environment and tunable electronic structure, which can achieve the combined advantages of homogeneous and heterogeneous catalysts. At the same time, the isolated sites in single atom catalysts can produce highly selective adsorption of specific substances, which shows great catalytic potential for the NO3RR process with complex intermediates.
[0005] The single-atom structure increases the surface free energy of the material. Although it improves the activity of the material, it also increases the tendency of single atoms to aggregate to form clusters or nanoparticles, which in turn leads to the inactivation of active sites. Therefore, it is of great significance to select a suitable substrate material to enhance the interaction between metal atoms and the substrate. Gel materials generally have a three-dimensional multi-level network structure. Their porous structure with high specific surface area can not only provide more active sites for anchoring metal atoms, but also limit the aggregation of metal atoms. By high-temperature treatment of gel materials with carbon-carbon covalent bonds (CC) or carbon-nitrogen covalent bonds (CN), porous graphitic carbon with high specific surface area, abundant exposed edges, high conductivity and high electrochemical stability can be obtained. It can be seen that gel-derived carbon materials are excellent carriers for efficiently anchoring metal atoms. Therefore, designing carbon-based single-atom catalysts based on gel materials is a very novel and worthy synthetic method. At present, copper-based catalysts show excellent activity in NO3RR. However, due to the lack of feasible preparation strategies, these copper single-atom catalysts have low metal loadings and ultimately unsatisfactory selectivity and yield for NO3RR. In addition, direct regulation of the microenvironment of single-atom sites by changing the cross-linker of the precursor remains a major challenge. Summary of the invention
[0006] The invention provides a preparation method of a pyridine nitrogen-rich copper single-atom catalyst and its application in electrocatalytic nitrate reduction to produce ammonia, which solves the problems of low catalytic efficiency and poor selectivity of existing catalysts.
[0007] In order to solve this technical problem, the present invention provides the following technical solution:
[0008] The preparation method of pyridine nitrogen-rich copper single atom catalyst comprises the following steps:
[0009] S1: Pyrrole monomer (pyrrole), polyethyleneimine (PEI) and sodium dodecylbenzene sulfonate (SDBS) are mixed and dissolved in HCl solution, which is marked as solution A.
[0010] S2 dissolves ammonium persulfate (APS) in HCl solution and is labeled as solution B;
[0011] S3: placing solution A and solution B in a refrigerator to cool, and after cooling, quickly mixing solution A and solution B, and placing the mixture in a refrigerator to stand to fully polymerize into a hydrogel;
[0012] S4: washing and purifying the polymerized hydrogel with ethanol and deionized water alternately. Dispersing the purified hydrogel in a CuCl2 solution and stirring overnight. Freeze-drying the hydrogel adsorbed with copper atoms in a freeze dryer. Afterwards, grinding the dried sample into a uniform powder;
[0013] S5: calcining the sample powder under argon atmosphere. After carbonization, the powder is added to HCl solution and allowed to stand to remove metal impurities;
[0014] S6 The acid-washed powder was washed with deionized water until neutral, and then dried in a vacuum drying oven. Finally, the obtained sample was carbonized for the second time under the same conditions to obtain a pyridine nitrogen-rich copper single atom catalyst, which was recorded as PR-CuNC;
[0015] S7 disperses PR-CuNC into a solution consisting of deionized water, isopropanol and Nafion binder.
[0016] Ultrasonic treatment. Then the dispersion is coated on the surface of carbon paper and dried naturally.
[0017] Preferably, in step S1, the volume of the pyrrole monomer is 416 μL, the mass of polyethyleneimine is 0.101 g, the mass of sodium dodecylbenzenesulfonate is 0.697 g, the concentration of HCl is 1.0 M, and the volume is 10 mL.
[0018] Preferably, the mass of ammonium persulfate in step S2 is 1.397 g, the concentration of HCl is 1.0 M, and the volume is 10 mL.
[0019] Preferably, in step S3, the cooling temperature is 2° C. and the standing time is 12 hours.
[0020] Preferably, the concentration of the CuCl2 solution in step S4 is 0.2M, the stirring time is 12 hours, and the freezing temperature of the freeze dryer is about -60°C.
[0021] Preferably, in step S5, the concentration of HCl is 0.5 M, the soaking time is 4 hours, and the soaking temperature is 80° C.
[0022] Preferably, the temperature of the vacuum drying oven in step S6 is 80°C.
[0023] Preferably, the step S7 specifically comprises: dispersing 3 mg of PR-CuNC into a solution consisting of 360 μL of distilled water, 120 μL of isopropanol and 20 μL of Nafion binder, ultrasonically treating for 15 min, and then dropping 20 μL of the dispersion onto the surface of the carbon paper.
[0024] This scheme also provides an electrode prepared with a pyridine nitrogen-rich copper single-atom catalyst, which is prepared by the above-mentioned preparation method.
[0025] This solution also provides the application of the above-mentioned electrode in electrocatalytic nitrate reduction to produce ammonia.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] This scheme provides a preparation strategy for regulating the coordination environment of single-atom catalyst sites, and prepares a pyridine-rich copper single-atom catalyst derived from polypyrrole / polyethyleneimine three-dimensional semi-interpenetrating hydrogel, which has significant NO3RR activity in an alkaline environment.
[0028] This scheme highlights the regulation strategy for the type of coordinated nitrogen atoms in copper single-atom catalysts. By directly introducing polyethyleneimine, a pyridine nitrogen-rich single-atom catalyst was synthesized. The coordination environment around the copper atom in the catalytic center was directly regulated at the molecular level, the electronic structure of the catalyst was effectively adjusted, and the intermediate reaction path of the catalytic process was improved, which is beneficial to improving the activity and selectivity of various electrocatalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0030] Figure 1 The schematic diagram of the preparation process of pyridine nitrogen-rich copper single atom catalyst and the NO3RR catalytic process on the Cu site;
[0031] Figure 2 For morphology characterization; among them, (a) is the SEM image of PR-CuNC; (b) is the HAADF-STEM image of PR-CuNC; (c) is the EDS mapping image of PR-CuNC;
[0032] Figure 3 is the XRD of PR-CuNC;
[0033] Figure 4For structural characterization; (a) is the XPS full spectrum of PR-CuNC; (b) is the XPS N1s fine spectrum of PR-CuNC; (c) is the Cu 2p spectrum of PR-CuNC;
[0034] Figure 5 XAFS characterization of PR-CuNC; (a) XANES of Cu foil, Cu2O, CuO, and PR-CuNC; (b) FT-EXAFS data of Cu foil, Cu2O, CuO, and PR-CuNC; (c) WT spectrum of PR-CuNC;
[0035] Figure 6 For electrochemical tests, (a) is the LSV test with and without 0.1M NO3ˉ in 0.1M KOH electrolyte; (b) is the It curve of constant potential test under different applied potentials;
[0036] Figure 7 The standard curve of the UV spectrophotometry test, (a) is the UV absorption spectrum of the standard ammonia concentration; (b) is the standard curve after fitting; (c) is the UV absorption spectrum of the standard nitrite concentration; (d) is the stability test of the standard curve after fitting PR-CuNC at -0.5V vs.RHE;
[0037] Figure 8 (a) Faradaic efficiency of ammonia; (b) is the yield of ammonia; (c) is the normalized yield of ammonia; (d) is the Faradaic efficiency of ammonia, nitrite and hydrogen;
[0038] Fig. 9 (a) Constant potential test curve of PR-CuNC; (b) Faradaic efficiency and yield of ammonia corresponding to the stability test;
[0039] Fig.10 (a) H NMR spectrum; (b) Ammonia produced under UV absorption spectrum and H NMR spectrum;
[0040] Fig.11 is the charge difference density of the two Cu-N4 models;
[0041] Fig.12 are the Cu d and N p orbital partial density of states (PDOS) of the two Cu-N4 models;
[0042] Fig.13 It is the intermediate structure of nitrate reduction to produce ammonia;
[0043] Fig.14 Gibbs free energy diagram for the nitrate reduction reaction to produce ammonia.
[0044] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. DETAILED DESCRIPTION
[0045] Example 1
[0046] (1) Preparation of PR-CuNC
[0047] First, 416 μL of pyrrole monomer (pyrrole), 0.101 g of polyethyleneimine (PEI) and 0.697 g of sodium dodecylbenzene sulfonate (SDBS) were dissolved in 10 mL of 1.0 M HCl aqueous solution, marked as solution A. 1.397 g of ammonium persulfate (APS) was added to 10 mL of 1.0 M HCl aqueous solution, marked as solution B. After cooling solution A and solution B to 2 °C, the two solutions were quickly mixed, and the mixture was placed in a refrigerator and allowed to stand at 2 °C for 12 hours to ensure sufficient polymerization to form a hydrogel. Finally, the polymerized hydrogel was washed alternately with deionized water and anhydrous ethanol several times to remove unreacted residual impurities and by-products. The purified hydrogel was freeze-dried at low temperature (about -60 °C) and low pressure (about 1.0 Pa). Afterwards, the dried sample was ground into a uniform powder and transferred to a porcelain boat. The sample powder was heated at 10 °C min under an argon atmosphere. -1 The powder was heated to 800°C at a rate of 1.5 °C and then kept at 800°C for 2 hours. After carbonization, the powder was added to a 0.5M HCl solution and allowed to stand at 80°C for 4 hours to remove metal impurities. The acid-washed powder was washed with deionized water to neutrality (pH = 7) and then dried in a vacuum oven at 80°C. Finally, the obtained sample was carbonized for the second time under the same conditions. The catalyst prepared by this method is named PR-CuNC.
[0048] Example 2
[0049] At room temperature, the electrochemical performance test was carried out by connecting the H-type electrolytic cell to the Donghua DH7003 electrochemical workstation. The H-type electrolytic cell was separated by a Nafion 115 ion exchange membrane with a size of 3.5 cm × 3.5 cm. Before the experiment, the Nafion membrane was soaked in a 5wt% hydrogen peroxide solution for 60 minutes, and the water bath heating temperature was 80°C. It was then heated in a water bath at 80°C in deionized water for 60 minutes. The working electrode was selected from the carbon paper of the PR-CuNC catalyst ink in Example 1. The geometric area of the carbon paper is 0.5×3cm 2 , the active area is 0.5×0.5cm 2. Hydrophobic carbon paper was soaked in ethanol and deionized water for 15 minutes and ultrasonically treated to remove surface impurities. 3 mg of catalyst powder and 20 μL of Nafion solution (5 wt%, Dupont, USA) were added to a mixture of deionized water (360 μL) and isopropanol (120 μL) and ultrasonically treated for 30 min to prepare catalyst ink. 20 μL of homogeneous catalyst ink was dropped on an active area of 0.25 cm 2 , mass loading is 0.48 mg cm -2 on a hydrophobic carbon paper. The other side of the carbon paper without the catalyst was sealed with an insulating hot melt adhesive to make the final working electrode. The electrochemical experiment was carried out using a three-electrode working system, with a saturated calomel electrode (SCE, 1M KCl) and a graphite rod as the reference electrode and counter electrode, respectively. Among them, the counter electrode was placed in the anode cell, and the reference electrode and the working electrode were placed in the cathode cell. 30mL of 0.1M KOH and 0.1M KNO3 solution were used as the cathode electrode solution, and the anode was 0.1M KOH solution. All potentials of the reference reversible hydrogen electrode (RHE) were obtained by the following calibration formula: E(RHE) = E(SCE) + 0.059 × pH + 0.253V. Before the electrochemical measurement, a pure argon gas flow was injected into the cathode electrolyte for 30 minutes to remove oxygen and nitrogen. All electrodes were cyclic voltammetry (CV) in the potential range of +0.5V to -0.9Vvs.RHE at 100mV s -1 The electrode was activated for 10 cycles at a scan rate of 10 mV s -1 Linear sweep voltammograms (LSVs) were obtained at a scan rate of +0.5 to -0.9 V relative to RHE. The current-time (It) curves at different potentials for 30 min were recorded by chronoamperometry, and the corresponding electrolytes were collected for calculating the NH3 yield and Faradaic efficiency.
[0050] Figure 1 The preparation process of Example 1 is shown. Specifically, PEI is introduced into pyrrole polymerization to form PPy-PEI hydrogel, in which PPy chains and PEI chains are uniformly interpenetrated. Thanks to the abundant primary and secondary amine groups of PEI, PPy-PEI hydrogel has a stronger ability to anchor Cu ions than pure PPy. Pyrrole and PEI cross-linking effectively improves the scarce nitrogen active sites and provides a diverse coordination environment. In addition, PPy-PEI hydrogel has a unique three-dimensional semi-interconnected nanostructure with abundant N sites and a large specific surface area, which is conducive to the adsorption of Cu ions and also prevents the aggregation of Cu particles during the subsequent carbonization process. Finally, the copper-adsorbed PPy-PEI hydrogel is subjected to secondary carbonization to obtain PR-CuNC, in which highly dispersed Cu atoms are anchored on the hydrogel-derived carbon substrate.
[0051] Figure 2 In (a), the scanning electron microscope image of Example 1 shows a porous particle structure composed of interconnected nanoparticles. Figure 2 As shown in (b), aberration correction was performed using a high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) to determine the distribution of atoms. The HAADF-STEM image of Example 1 shows light spots scattered on the edge and surface of the carbon substrate. Since the atomic mass of the Cu element in the catalyst is much greater than that of other elements (C, N, O), it can be determined that the light spots represent isolated Cu single atoms. Figure 2 In (c), energy dispersive X-ray spectroscopy (EDS mapping) mapping analysis further confirmed the uniform dispersion of Cu, N, and C elements in Example 1, indicating that Cu atoms are uniformly distributed on the nitrogen-doped carbon substrate.
[0052] exist Figure 3 In the XRD spectrum of Example 1, there is a broad peak at 25.6°, corresponding to the (002) plane of graphite carbon, and no diffraction peak of the Cu-based crystalline phase is observed. Therefore, there are no aggregated Cu-based compounds in PR-CuNC, and the Cu species are mainly amorphous.
[0053] The elemental composition and valence state of the catalyst were determined by X-ray photoelectron spectroscopy (XPS). Based on the XPS spectrum, the elemental composition and atomic ratio of Example 1 were determined ( Figure 4 a) The atomic ratio of N element in PR-CuNC is 8.21%, which can be attributed to the presence of PEI with abundant amine groups. Figure 4 As shown in (b), the high-resolution N1s XPS spectrum of Example 1 can be divided into four peaks, namely pyridine-N (398.2eV), pyrrole-N (399.3eV), graphite-N (400.8eV) and oxide-N (401.7eV). The absolute content of each nitrogen structure was calculated, among which the absolute content of pyridine-N was 3.20%, and the absolute content of pyrrole-N was 0.76%. This shows that the introduction of PEI successfully synthesized a catalyst with richer pyridine nitrogen structure. Figure 4 (c) Cu 2p XPS spectrum of Example 1, showing that Cu 2p 3 / 2 and Cu 2p 1 / 2 The XPS characteristic peaks at 934.55 and 954.40 eV correspond to Cu(II), and the XPS characteristic peaks at 932.40 and 952.14 eV correspond to Cu(I) / Cu(0). The content of Cu in Example 1 was more accurately determined to be 6.01 wt% by inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0054] Considering the limitations of XPS in characterizing precise structures, we further analyzed the fine structure of Example 1 by X-ray absorption fine structure (XAFS) spectroscopy to obtain more accurate coordination structure information at the atomic scale. Cu foil, Cu2O and CuO were selected as standard reference calibration samples for the test. Figure 5 (a) shows the normalized Cu K-edge X-ray absorption near-edge structure (XANES) spectra of PR-CuNC, Cu foil, Cu2O, and CuO. Compared with Cu2O and Cu foil, the adsorption edge of PR-CuNC is located in the high-energy region near CuO, indicating that the Cu atoms are in an oxidized state. The first-order derivative of PR-CuNC is between that of Cu2O and CuO ( Figure 5 a inset), which confirms that the Cu valence state of PR-CuNC is between +1 and +2, which is consistent with the Cu 2p XPS observations of PR-CuNC. Fourier transform X-ray absorption fine structure (FT-EXAFS) spectra were obtained to verify the precise structure of Cu atoms in PR-CuNC, such as Figure 5 Compared with copper foil, Cu2O and CuO, PR-CuNC only shows a The single peak centered at belongs to the Cu-N bond. In addition, Figure 5 (c) is the wavelet transform (WT) diagram of Example 1. The only maximum intensity of PR-CuNC is at The positions are assigned to the Cu-N bonds, indicating that there is a strong interaction between the Cu atoms and the carbon substrate, and the copper atoms and nitrogen atoms coordinate with each other to form uniformly dispersed copper single atoms.
[0055] To investigate the effect of catalyst sizes on NO3RR activity, the electrocatalytic performance of PR-CuNC in 0.1M KOH and 0.1M KNO3 was evaluated. Figure 6 As shown in (a), first, linear sweep voltammetry (LSV) tests were performed in 0.1M KOH solutions with and without 0.1M KNO3. In the electrolyte without nitrate, the current was mainly generated by the hydrogen evolution side reaction. After adding 0.1M KNO3, the scanning current increased significantly, indicating that nitrate reduction occurred. The current began to change significantly at -0.3V vs. RHE, and the main reason for the increase in current was due to nitrate reduction. PR-CuNC began to reduce nitrate at +0.1V, and the current density was as high as 90mA cm at -0.9V. -2 , showing excellent electrocatalytic nitrate reduction activity.
[0056] To further evaluate the NO3RR performance, the current density-time (It) curves of PR-CuNC in the range of −0.1 to −0.6 V vs. RHE were recorded ( Figure 6b), and the amount of NH3 produced was determined by ultraviolet spectrophotometry and calculation of the Faradaic efficiency (FE) and yield (YR). The standard curve of ammonia and the main byproduct nitrite is shown in Figure 7 (ad) PR-CuNC reaches a maximum FE of 94.61% at -0.5V vs. RHE ( Figure 8 a), the corresponding yield is 3.74 mg NH3 h -1 cm -2 ( Figure 8 b) To avoid the influence of Cu content, the active sites were normalized to copper, e.g. Figure 8 (c) shows the YR of PR-CuNC at -0.5 V. Cu 130.71 mg NH3 mg Cu -1 h -1 , showing excellent activity. The nitrate reduction reaction includes complex intermediates and by-products, such as Figure 8 (d) shows the determination of the main by-product nitrite (NO2 - ) and hydrogen (H2). NO2 - is the main product of PR-CuNC at low overpotential. As more negative potential is applied, NO2 - The FE of PR-CuNC decreases gradually. In addition, the competitive HER affects the NH3 selectivity at -0.4 V, and the Faradaic efficiency reaches a maximum of 6.92% at -0.6 V on PR-CuNC.
[0057] Using the same electrode, 10 consecutive electrolysis experiments were carried out at -0.5 V vs. RHE and the It curves were recorded ( Fig. 9 a). After 10 cycles, FE is always above 85% and YR is stable at 120 mg NH3 mg Cu -1 h -1 above( Fig. 9 b) In addition, 15 N isotope labeled proton NMR resources ( 1 H NMR) verifies the accuracy of NH3 measurement and eliminates possible ammonia contamination from the environment. 14 NO3 - and 15 NO3 - Electrochemical experiments were performed as N sources, and maleic acid was used as an internal standard to quantify the generated NH3. Fig.10 As shown in a, from 14 NO3 - The NMR spectrum of the product obtained with N as the source showed 14NH4 + There are three peaks with an interval of 52Hz. 15 NO3 - The NMR spectrum measured for the N source showed 15 NH4 + It is a characteristic double peak with an interval of 72Hz. Fig.10 bIt can be seen that 15 NH4 + The yield (17.04 μmol) and 14 NH4 + The yield of NH3 (16.92 μmol) is very close to that of NH3 (16.92 μmol), indicating that the measured NH3 only comes from the electrocatalytic nitric acid process. The ammonia content determined by 1HNMR method (16.92 μmol) is comparable to that determined by UV-Vis method (16.96 μmol), confirming the reliability of the results of UV spectrophotometry.
[0058] In order to further understand the reaction mechanism of the excellent nitrate selectivity of pyridinium-rich N-type Cu single atom catalyst, density functional theory (DFT) calculations were used to study its structure-activity relationship. A Cu-N4 catalyst model was constructed, in which the Cu single atom was coordinated with four pyridinic-N (Cu-pyridinic-N4) and four pyridinic-N (Cu-pyrrolic-N4). The charge difference density of the above two Cu-N4 models is shown in Figure 2. Fig.11 As shown in Figure 2, they depict distinctly different charge distributions. Compared to Cu-pyridinic-N4, Cu-pyrrolic-N4 shows electron depletion around Cu atoms and stronger electron accumulation around C atoms bonded to N. The partial density of states (PDOS) of Cu-pyridinic-N4 and Cu-pyrrolic-N4 are shown in Figure 2. Fig.12 Compared with Cu-pyridinic-N4, the Cu d orbital of Cu-pyrrolic-N4 has obvious energy level splitting near the Fermi level and negative shift of the active center. Cu-pyridinic-N4 is more conducive to electron transfer due to the obvious hybridization between Cu d and N p orbitals and the higher electron density overlap area on the bonding orbital, which is beneficial to the adsorbed NO3 - The different distributions of the density of states indicate that the electronic structure of Cu-N4 is regulated by the type of coordinated N.
[0059] The intermediates of NO3RR on the two model surfaces were further analyzed in detail by Gibbs free energy calculations. Fig.13 ) and reaction pathway ( Fig.14). Specifically, compared with Cu-pyrrolic-N4, Cu-pyridinic-N4 has a good NO3ˉ adsorption capacity in the first step of NO3RR. Then, * NO3 is gradually produced by NO decomposition * NO2 and * NO. In the subsequent hydrogenation process from *NO to *NHO, a large energy barrier needs to be overcome. The energy barrier of Cu-pyridinic-N4 is +0.07eV, which is lower than +0.51eV of Cu-pyrrolic-N4, indicating that Cu-pyridinic-N4 has a stronger protonation activity for *NO. * NO formation * NHO, * NH2O and * NH2OH. Finally, * NH2OH undergoes another NO cracking and hydrogenation process to generate * NH3, * The final NH3 molecule can be obtained by desorption of NH3 from the catalyst surface. In general, except for the *NHO generation step which is considered to be the rate-limiting reaction, the NO3RR reactions on both Cu-N4 models are exothermic. - Both the adsorption capacity and the lower energy barrier indicate that the Cu-pyridinic-N4 structure is more favorable for NO3 - Synthetic ammonia.
[0060] A hydrogel-derived pyridinic N-rich Cu single-atom catalyst was synthesized by adjusting the structure of coordinated N atoms. The absolute content of pyridinic N reached 3.20% by forming a semi-interpenetrating PPy-PEI hydrogel with abundant N sites. Under low overpotential conditions, PR-CuNC achieved NO3 - Efficient reduction to NH3, with a maximum Faradaic efficiency of 94.61% and a yield of 130.71 mg NH3 mg Cu -1 h -1 By NO3 - Through reduction experiments and DFT calculations, we found that different types of coordinated nitrogen atoms effectively regulated the electronic structure between Cu and N atoms. The high NO3RR activity and selectivity exhibited by PR-CuNC originated from the coordination of single-atom Cu sites with pyridine-N atoms. This project proposed a synthetic strategy for directly regulating the local microenvironment of single-atom catalysts at the molecular scale.
[0061] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a pyridine-nitrogen-rich copper single-atom catalyst, characterized in that: S1: Pyrrole monomer (pyrrole), polyethyleneimine (PEI) and sodium dodecylbenzene sulfonate (SDBS) are mixed and dissolved in HCl solution, which is marked as solution A. S2 dissolves ammonium persulfate (APS) in HCl solution and is labeled as solution B; S3: placing solution A and solution B in a refrigerator to cool, and after cooling, quickly mixing solution A and solution B, and placing the mixture in a refrigerator to stand to fully polymerize into a hydrogel; S4: washing and purifying the polymerized hydrogel with ethanol and deionized water alternately, dispersing the purified hydrogel in a CuCl2 solution and stirring overnight, freeze-drying the hydrogel adsorbing copper atoms in a freeze dryer, and grinding the dried sample into a uniform powder; S5: calcining the sample powder under argon atmosphere, and after carbonization, adding the powder into HCl solution and standing to remove metal impurities; S6: The acid-washed powder is washed with deionized water until neutral, and then dried in a vacuum oven. The obtained sample is carbonized for the second time under the same conditions to obtain a pyridine nitrogen-rich copper single atom catalyst, which is denoted as PR-CuNC. S7 dispersed PR-CuNC into a solution consisting of deionized water, isopropanol and Nafion binder, and ultrasonicated. The dispersion was then applied to the surface of carbon paper and allowed to dry naturally.
2. The method for preparing a pyridine-nitrogen-rich copper single-atom catalyst according to claim 1, wherein the volume of the pyrrole monomer in step S1 is 416 μL, the mass of polyethyleneimine is 0.101 g, the sodium dodecylbenzenesulfonate is 0.697 g, the concentration of HCl is 1.0 M, and the volume is 10 mL.
3. The method for preparing a pyridine-nitrogen-rich copper single-atom catalyst according to claim 1, wherein the mass of the ammonium persulfate in step S2 is 1.397 g, the concentration of HCl is 1.0 M, and the volume is 10 mL.
4. The method for preparing a pyridine nitrogen-rich copper single-atom catalyst according to claim 1, wherein the cooling temperature in step S3 is 2°C and the standing time is 12 hours.
5. The method for preparing a pyridine nitrogen-rich copper single-atom catalyst according to claim 1, wherein the concentration of the CuCl2 solution in step S4 is 0.2 M, the stirring time is 12 hours, and the freezing temperature of the freeze dryer is about -60°C. 6 . The method for preparing a pyridine nitrogen-rich copper single-atom catalyst according to claim 1 , wherein the concentration of HCl in step S5 is 0.5 M, the soaking time is 4 hours, and the soaking temperature is 80° C. 7 . The method for preparing a pyridine nitrogen-rich copper single-atom catalyst according to claim 1 , wherein the temperature of the vacuum drying oven in step S6 is 80° C.
8. The method for preparing a pyridine nitrogen-rich copper single atom catalyst according to claim 1, wherein step S7 is specifically: dispersing 3 mg of PR-CuNC into a solution consisting of 360 μL of distilled water, 120 μL of isopropanol and 20 μL of Nafion binder, ultrasonically treating for 15 minutes, and then dropping 20 μL of the dispersion onto the surface of carbon paper.
9. An electrode of a pyridine nitrogen-rich copper single-atom catalyst, characterized in that: It is prepared by the preparation method according to claims 1-7.
10. Use of the electrode according to claim 8 in producing ammonia by nitrate reduction.
Citation Information
Patent Citations
Three-dimensional porous carbon nitride-based Zn monatomic photocatalyst, preparation method and application
CN114984997A
Preparation method and application of monatomic Fe-N-C catalyst
CN115360369A
Cited By
Iron-manganese diatomic catalyst modified by iron cluster as well as preparation method and application of iron-manganese diatomic catalyst
CN120119287A
Catalyst capable of being used for preparing ammonia gas by reducing nitrate as well as preparation method and application of catalyst
CN120485820A
Catalyst for reduction of nitrate to produce ammonia, and preparation method and application thereof
CN120485820B